MENINGKATKAN HASIL BELAJAR TEMA 4 GLOBALISASI MENGGUNAKAN METODE BERMAIN PERAN DI KELAS VI SDN 11 PEKAN TOLAN TAHUN PELAJARAN 2021/2022 - Hotib, Timbul Amar (Jurnal Tematik, 2022)
This research was conducted on sixth grade students of SD Negeri 11 Pekan Tolan in the 2021/2022 academic year. According to the results of observations that grade VI students' learning scores on Theme 4 Globalization are very low. The purpose of this study was to describe learning outcomes using the role playing method. The method used is a descriptive method with the type of Classroom Action Research (CAR), each cycle begins with planning, observation, action, and reflection. of 67.19, and the average class in cycle 2 is 75.00. This proves that the average pre-cycle compared to cycle 1 has increased by 10.40, while the class average between cycle 1 compared to cycle 2 is 7.81. The percentage of completeness in the pre-cycle was 56%, the first cycle was 71.86%, the second cycle was 87.50%. This means that between pre-cycle compared to cycle 2, there was an increase of 15.61%, while completeness in cycle 1 compared to cycle 2 was 15.64%. The number of students who completed according to the KKM in the pre-cycle were 17 people, in cycle 1 as many as 23 people, and in cycle 2 as many as 28 people. this experienced an increase in completeness between the pre-cycle compared to the additional cycle as many as 6 people, and an increase in completeness between cycle 1 compared to cycle 2 as many as 5 people